Perfused heart studies to investigate lipid metabolism. (February 2000) - Evans, R. D.; Bennett, M.J.; Hauton, D.
Abstract : The isolated perfused heart preparation is an invaluable model for investigating metabolism in a variety of physiological and pathological states. It avoids confounding systemic factors (e.g. endocrine, metabolic and work load changes) and permits simultaneous measurement of mechanical function. The ability to measure arteriovenous concentration differences across the myocardium and the coronary flow rate, together with the use of radiolabelled substrates, permits assessment of substrate assimilation and disposition of most potential energetic substrates. In the case of lipids, metabolism of non-esterified fatty acids has been extensively investigated in the perfused rat heart, but fatty acids may also be derived from circulating triacylglycerols (TAG) in lipoproteins [chylomicrons, very-low-density-lipoprotein (VLDL)]. TAG requires initial hydrolysis by the endothelial enzyme lipoprotein lipase and hence an intact heart preparation is vital to maintain tissue structural integrity. Chylomicron-TAG utilization and fate (oxidation, tissue-lipid deposition) in isolated working hearts has been studied using chylomicrons obtained from thoracic-duct catheters. However, lack of availability of sufficient quantities of VLDL has hindered examination of their cardiac utilization; the recent development of a technique to produce large quantities of radiolabelled rat VLDL has facilitated these studies and established that VLDL-TAG is an important metabolic substrate for working heart. Results relating to myocardial utilization of VLDL-TAG under varying physiological (lactation) and pathological (endotoxinaemia) conditions will be presented. The putative role of VLDL as a regulator of cardiac lipid metabolism will also be discussed.